A Comparison of Prabowo Subianto's Political Rhetoric on Human Rights Issues in the Presidential Candidate Debates of the 2019 and 2024 General Elections - Zullfikar, Zamri; Bahri, Syaiful (Journal Ilmu Sosial, Politik dan Pemerintahan, 2026)
This study compares the political rhetoric of Prabowo Subianto in the presidential candidate debates of the 2019 and 2024 elections concerning Human Rights (HAM) issues, using Charles Sanders Peirce's semiotic theory. The findings reveal a significant shift from assertive and formal rhetoric in 2019 to a more relaxed and humorous style in 2024. This transformation was influenced by semiotic dimensions, including clothing choices, verbal and non-verbal expressions, and the individuals seated in the supporters' row, all of which reinforced the shift in Prabowo's rhetoric between the 2019 and 2024 presidential debates. This study affirms the importance of rhetorical analysis that not only focuses on words but also takes into account the surrounding semiotic context.